ACCURACY OF CONTOURING BY NEURO-ONCOLOGISTS FOR DELIVERY OF FRACTIONATED STEREOTACTIC RADIOTHERAPY (FSRT) AND STEREOTACTIC RADIOSURGERY (SRS) FOR BENIGN INTRACRANIAL CONDITIONS; WHAT DO THE NEURO-RADIOLOGIST AND NEURO-SURGEON ADD?. (3rd October 2018) - Hobbs, Claire; Pretorius, Pieter; Joseph, Robin; Jeyaretna, Sanjeeva; Warner, Nicola; Padmanaban, Sriram; Tunstall, Clare; Watson, Rhona
Abstract: Variability exists between clinical oncologists when contouring gross tumour volume (GTV) and normal tissue organs at risk (OAR) volumes. This variability is the 'weakest link' in the context of the highly conformal and highly accurate treatment delivery used for SRS and fSRT. In 2016-17NHS England commissioned 17 SRS centres. The service specification mandates "treatment protocols will ensure that target definition is performed by either a sub-specialised neuro-surgeon and / or neuro-oncologist (clinical oncologist) with input from a neuro-radiologist before a treatment plan is created." To evaluate the additional contribution by the neuro radiologist we analysed contouring conformality for 90 patients with benign conditions treated in our centre (September 2014 – February 2018) using fSRT or SRS. GTV margins contoured by the clinical oncologist were copied and amended with the neuro-radiologist and sometimes neurosurgeon. Clinical target volumes (CTV) were added depending on the tumour type and grade, 1 mm margin was added to CTV for the planning target volume (PTV). The 90 patients included 71 meningioma, 10 pituitary adenoma, 6 craniopharyngioma, 3 other. Doses used were: 45–59.4 Gy in 30–33 fractions for fSRT and 14-16Gy for SRS. We used Eclipse TPS (v13.7) for Varian (Palo Alto, CA) Clinac iX with millennium MLC (5 mm) and Exactrac imaging system (Brainlab, Munich DE). All plans were created either using dynamic conformal arc (DCA) or VMAT RapidArc (RA) techniques with 6 MV photons and calculated using AAA (v10) on a 1 mm dose grid. Values for the final treated GTV and PTV (A) were compared with the GTV and PTV that were generated by the Clinical oncologist alone (B) will be compared using the Conformity analysis consisted of Jaccard coefficient, Dice coefficient, Geographical Miss and Discordance index as defined below. Results will be presented.